Examination of archived rusticles from World War II shipwrecks. (September 2019) - Little, Brenda J.; Lee, Jason S.; Briggs, Brandon R.; Ray, Richard; Sylvester, Andrew
Abstract: The authors examined the physiochemical and microbiological properties of archived rusticles from World War II shipwrecks in the Gulf of Mexico. Rusticles, iron (Fe)-rich accumulations on shipwrecks in marine environments, have long been assumed to be the result of low alloy steel corrosion. In many cases the assumed corrosion has been attributed to biodeterioration because of the presence of specific types of bacteria associated with the rusticles. However, archived rusticles from WWII shipwrecks in the Gulf of Mexico (GOM) do not have the mineralogical layering typical of iron corrosion products. Moreover, spatial relationships between bacteria and rusticles cannot be interpreted as biodeterioration. The authors concluded that environmental Fe plays a role in rusticle formation and differences in Fe concentrations can be used to explain differences in rusticle size and distribution with depth in the GOM. Both biotic and abiotic mechanisms for Fe accumulation are provided. Highlights: Rusticles are iron-rich accumulations found on shipwrecks in marine environments. The spatial relationship between microorganisms and accumulated iron oxides cannot be interpreted as biodeterioration. Rusticles from Gulf of Mexico shipwrecks are not consistent with mineralogical layering typical of iron corrosion products. The role of environmental iron in rusticle formation and growth has been previously ignored.